2022
DOI: 10.1101/2022.12.21.519945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STAT5 Gain-of-Function Variants Promote Precursor T-Cell Receptor Activation to Drive T-Cell Acute Lymphoblastic Leukemia

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive immature T-cell cancer. Hotspot mutations in JAK-STAT pathway members IL7R, JAK1 and JAK3 were analyzed in depth. However, the role of STAT5A or STAT5B mutations promoting their hyperactivation is poorly understood in the context of T-cell cancer initiation and acute leukemia progression. Importantly, the driver mutation STAT5BN642H encodes the most frequent activating STAT5 variant in T-ALL associated with poor prognosis. Here, we show that hyperact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Astonishingly, only one replication of H9RET retained activation of ADGRE5, H9RETR and the control groups all failed, while IL32 remained strongly enriched under both conditions, which indicated that the regulation of STAT5 by ADGRE5 was stricter than that by IL32. Nevertheless, IL2-mediated STAT5 activation provides indirect evidence to some extent, and we further reanalyzed DEGs from Tobias et al They constructed the "gain-of-function" mutations STAT5A N642H and STAT5B S710F in CD8 + T cells via CRISPR/Cas9 and performed bulk RNA-seq on wild-type CD8 + T cells (97). Again, ADGRE5 was upregulated in STAT5 N642H and STAT5 S710F cells (Figure 3L), further confirming the positive regulatory effect of STAT5 on ADGRE5.…”
Section: Multimodal Analysis Revealing Stat5 Regulation Of Adgre5mentioning
confidence: 99%
“…Astonishingly, only one replication of H9RET retained activation of ADGRE5, H9RETR and the control groups all failed, while IL32 remained strongly enriched under both conditions, which indicated that the regulation of STAT5 by ADGRE5 was stricter than that by IL32. Nevertheless, IL2-mediated STAT5 activation provides indirect evidence to some extent, and we further reanalyzed DEGs from Tobias et al They constructed the "gain-of-function" mutations STAT5A N642H and STAT5B S710F in CD8 + T cells via CRISPR/Cas9 and performed bulk RNA-seq on wild-type CD8 + T cells (97). Again, ADGRE5 was upregulated in STAT5 N642H and STAT5 S710F cells (Figure 3L), further confirming the positive regulatory effect of STAT5 on ADGRE5.…”
Section: Multimodal Analysis Revealing Stat5 Regulation Of Adgre5mentioning
confidence: 99%